Impact of New Motor Deficit on HRQOL After Adult Spinal Deformity Surgery: Subanalysis From Scoli Risk 1 Prospective Study. Issue 7 (1st April 2021) - Saigal, Rajiv; Lau, Darryl; Berven, Sigurd H.; Carreon, Leah; Dekutoski, Mark B.; Kebaish, Khaled M.; Qiu, Yong; Matsuyama, Yukihiro; Kelly, Michael; Dahl, Benny T.; Mehdian, Hossein; Pellisé, Ferran; et al.
Abstract : Study Design: International, multicenter, prospective, longitudinal observational cohort. Objective: To assess how new motor deficits affect patient reported quality of life scores after adult deformity surgery. Summary of Background Data: Adult spinal deformity surgery is associated with high morbidity, including risk of new postoperative motor deficit. It is unclear what effect new motor deficit has on Health-related Quality of Life scores (HRQOL) scores. Methods: Adult spinal deformity patients were enrolled prospectively at 15 sites worldwide. Other inclusion criteria included major Cobb more than 80°, C7–L2 curve apex, and any patient undergoing three column osteotomy. American Spinal Injury Association (ASIA) scores and standard HRQOL scores were recorded pre-op, 6 weeks, 6 months, and 2 years. Results: Two hundred seventy two complex adult spinal deformity (ASD) patients enrolled. HRQOL scores were worse for patients with lower extremity motor score (LEMS). Mean HRQOL changes at 6 weeks and 2 years compared with pre-op for patients with motor worsening were: ODI (+12.4 at 6 weeks and –4.7 at 2 years), SF-36v2 physical (–4.5 at 6 weeks and +2.3 at 2 years), SRS-22r (0.0 at 6 weeks and +0.4 at 2 years). Mean HRQOL changes for motor-neutral patients were: ODI (+0.6 at 6 weeks and –12.1 at 2 years), SF-36v2 physical (–1.6 at 6 weeks and +5.9 at 2 years), and SRS-22r (+0.4 at 6 weeks and +0.7 at 2 years). For patients with LEMS improvement, mean HRQOL changes were: ODI (–0.6 at 6 weeks and –16.3 at 2 years), SF-36v2 physical (+1.0 at 6 weeks and +7.0 at 2 years), and SRS-22r (+0.5 at 6 weeks and +0.9 at 2 years). Conclusion: In the subgroup of deformity patients who developed a new motor deficit, total HRQOLs and HRQOL changes were negatively impacted. Patients with more than 2 points of LEMS worsening had the worst changes, but still showed overall HRQOL improvement at 6 months and 2 years compared with pre-op baseline. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textAn international, multicenter, ambispective, cohort study was completed to study effect of motor deficit on Health-related Quality of Life scores (HRQOLs) after adult spinal deformity surgery. HRQOLs were lower in patients who had more than 2 points of lower extremity motor score worsening. However, even these patients showed overall HRQOL improvement at 2 years.